2011
DOI: 10.1371/journal.pone.0025571
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Viremia as a Risk Factor for Mortality Prior to Antiretroviral Therapy among HIV-Infected Gold Miners in South Africa

Abstract: BackgroundCytomegalovirus (CMV) viremia has been shown to be an independent risk factor for increased mortality among HIV-infected individuals in the developing world. While CMV infection is nearly ubiquitous in resource-poor settings, few data are available on the role of subclinical CMV reactivation on HIV.MethodsUsing a cohort of mineworkers with stored plasma samples, we investigated the association between CMV DNA concentration and mortality prior to antiretroviral therapy availability.ResultsAmong 1341 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
5
32
2
3
Order By: Relevance
“…This is similar to the threshold VL that is commonly used in stem cell transplant patients at high risk of CMV reactivation [7]. This threshold is supported by the findings of recent studies, which noticed an association between CMV VL and high mortality in ambulatory patients with HIV/AIDS [16][18]. Death hazard ratios of 3.65 and 3.9 were reported by Fielding et al and Boffi El Amari et al, respectively, when the CMV VL was ≥1000 copies/ml [16], [17]; while Durier et al reported a death hazard ratio of 7.28 when the CMV VL was >500 copies/ml [18].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is similar to the threshold VL that is commonly used in stem cell transplant patients at high risk of CMV reactivation [7]. This threshold is supported by the findings of recent studies, which noticed an association between CMV VL and high mortality in ambulatory patients with HIV/AIDS [16][18]. Death hazard ratios of 3.65 and 3.9 were reported by Fielding et al and Boffi El Amari et al, respectively, when the CMV VL was ≥1000 copies/ml [16], [17]; while Durier et al reported a death hazard ratio of 7.28 when the CMV VL was >500 copies/ml [18].…”
Section: Discussionsupporting
confidence: 84%
“…This threshold is supported by the findings of recent studies, which noticed an association between CMV VL and high mortality in ambulatory patients with HIV/AIDS [16][18]. Death hazard ratios of 3.65 and 3.9 were reported by Fielding et al and Boffi El Amari et al, respectively, when the CMV VL was ≥1000 copies/ml [16], [17]; while Durier et al reported a death hazard ratio of 7.28 when the CMV VL was >500 copies/ml [18]. A recently published study, which employed a CMV VL threshold of 5000 copies/ml (and 3000 copies/ml for certain patients) showed that pre-emptive therapy prevents CMV end-organ disease by almost 25% in HIV infected patients with advanced immunosuppression [19].…”
Section: Discussionsupporting
confidence: 83%
“…Tanto la positividad de la antigenemia como de la RPC-TR detectadas en este estudio se incluyen en el rango de publicaciones extranjeras para el diagnóstico de enfermedad por CMV en portadores de VIH (33-100% de la antigenemia y 5,2-35% de la RPC) 12,[22][23][24][25][26][27] . A nivel nacional, nuestros resultados sólo pueden compararse con lo publicado en receptores de trasplantes 16-18 , en quienes la positividad de la antigenemia (40%) y de la RPC (> 32%) 17,18 fueron mayores, en especial en pacientes que recibieron un trasplante de órganos sólidos con sospecha clínica de enfermedad (58% de la antigenemia y 73% de la RPC) 16 , aunque la concordancia fue moderada (κ = 0,57) y menor a la de este estudio.…”
Section: Discussionunclassified
“…A nivel nacional, nuestros resultados sólo pueden compararse con lo publicado en receptores de trasplantes 16-18 , en quienes la positividad de la antigenemia (40%) y de la RPC (> 32%) 17,18 fueron mayores, en especial en pacientes que recibieron un trasplante de órganos sólidos con sospecha clínica de enfermedad (58% de la antigenemia y 73% de la RPC) 16 , aunque la concordancia fue moderada (κ = 0,57) y menor a la de este estudio. Diferencias en los cuadros clínicos, recuentos de LT CD4 y TARV de los pacientes enrolados-factores que inciden en la frecuencia de enfermedad por este virus, técnicas de amplificación y valores umbrales aplicados para definir resultados positivos (entre 900 y 1,6 x 10 5 copias referidos a 10 5 o 10 6 céls o LPMN o por ml de LPMN o leucocitos) 5,[24][25][26][27][28] dificultan las comparaciones y enfatiza la necesidad de establecer en nuestro país la positividad de las técnicas disponibles en cada población de inmunocomprometidos, idealmente utilizando RPC universales. La concordancia aceptable entre la antigenemia y la RPC-TR en los enfermos concuerda con lo publicado a nivel internacional (κ entre 0,4 y 0,9) 10,29 .…”
Section: Discussionunclassified
“…O CMV é um vírus oportunista que causa uma das maiores incidências de morbidade e mortalidade em pacientes portadores de HIV no mundo (CINQUE et al, 1992), não somente devido a sua patogenicidade, mas também devido ao seu papel na progressão da infecção pelo HIV (FIELDING et al, 2011). Em cerca de 90% dos casos, pode levar a sérias complicações, sendo a retinite uma das formas mais graves ( JABS, 2011).…”
Section: Eraldo Schunk Silvaunclassified